PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMK NEGERI 3 PADANG - Fitri, Fara Salsa Billah; Alfiriani, Adlia; Novita, Rini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The problem in this study is that the teaching aids used are still in the form of computer applications such as PowerPoint and textbooks that can help students in carrying out learning activities. Furthermore, based on the results of the interviews conducted, some students have difficulty understanding computer devices. Students are allowed to bring smartphones to school, the initial purpose of which is for students to use them to search for additional learning materials. However, in reality, it can be observed that students tend to use smartphones only as entertainment media, such as playing social media and online games. The purpose of this study is to create valuable and practical augmented reality educational media for computer science subjects in grade 10. Based on the results of research and discussion on the development of augmented reality educational media in grade 10 science subjects, augmented reality educational media was developed through the stages of analysis, design, development, implementation, evaluation, and dissemination. The validity test of the augmented reality educational media developed obtained an average media validity value of 83.7% which can be classified as "Very valid". The material validity test obtained an average value of 97.2% with the category "Very valid". Practical testing of the developed augmented reality teaching media obtained a practical value of 97.2% for teachers with the category "Very practical". Student practicality achieved an average score of 89.4% which can be classified as "Very Practical".